HUBUNGAN PERSEPSI KADER KESEHATAN TENTANG SEKOLAH KADER DENGAN KEPUASAN KADER KESEHATAN DI DUSUN SOKA SELOHARJO PUNDONG BANTUL TAHUN 2024 - Dian Novita Kumalasari; Eni Purwaningsih; Supatmi; Erma Pranawati (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
The perception of health cadres towards cadre schools significantly impacts the satisfaction level of health cadres. Training and maintenance of health cadres are important factors in improving their performance and satisfaction. Cadre training can also enhance communication skills and satisfaction with their role as cadres. This study aims to explore and understand the relationship between health cadres' perception of cadre schools and the level of satisfaction among health cadres in Dusun Soka Seloharjo Pundong Bantul. This study utilizes a Cross-Sectional design, and for bivariate analysis, Pearson Correlation is employed to determine the relationship between health cadres' perception of cadre schools and the level of satisfaction among health cadres. The research was conducted from January to February 2024. The results indicate a significant relationship between health cadres' perception of cadre schools and the level of satisfaction among health cadres. Data analysis reveals a strong positive relationship between health cadres' perception of cadre schools and their satisfaction level. Health cadres with positive perceptions of cadre schools tend to have higher satisfaction levels with the training programs they receive. Several factors from health cadres' perceptions of cadre schools that significantly impact their satisfaction levels have been identified. Positive perceptions of health cadres towards cadre schools are closely related to their satisfaction level with the training programs received. Health cadres with positive perceptions tend to be more satisfied with these programs.